Aluminum electrolytic capacitor sintered foil and preparation method thereof
By adding europium salt and ammonium hydroxide to the aluminum powder dispersion and using sodium hydride during sintering and shaping, the problem of difficult to control the formation of oxide layer in the sintered foil of aluminum electrolytic capacitor is solved, and the performance of specific capacitance and composite oxide film is improved.
Patent Information
- Application Number
- CN202510053934.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-29
AI Technical Summary
The sintered foil of the existing aluminum electrolytic capacitors is difficult to control the formation of the oxide layer during the sintering and shaping process, resulting in a decrease in the specific capacitance of the anode foil.
By adding europium salt and ammonium hydroxide to the dispersion of aluminum powder, an europium element film is formed, and sodium hydride is added during subsequent sintering and decomposition to form a reducing atmosphere, reducing the content of the single oxide film and increasing the proportion of the composite oxide film.
The specific capacitance of the aluminum electrolytic capacitor is improved, the corrosion resistance and dielectric properties of the composite oxide film are enhanced, and the thickness of the oxide film is reduced.
Smart Images

Figure CN119905353A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrode foil sintering, and in particular to an aluminum electrolytic capacitor sintered foil and a preparation method thereof. Background Art
[0002] Aluminum electrolytic capacitors are mainly composed of electrode foil, electrolytic paper, and electrolyte. The electrode foil is composed of aluminum foil with a high specific surface area and an oxide film on its surface. Its thickness determines the distance between the positive and negative electrodes and the voltage resistance of the capacitor. According to existing development research, the specific capacitance of the oxide film is inversely proportional to the voltage it withstands. Therefore, most of the capacitor's voltage resistance is borne by the anode foil. Therefore, in order to increase the specific capacitance of the anode foil, the thickness of the anodized film is mainly reduced. However, in order to prevent the oxide film from being punctured, it cannot be too thin. The second point is to increase the dielectric constant of the oxide film, mainly by adding composite materials, but this step is complex and costly. The third point is to increase the surface area of the aluminum foil, thereby increasing the specific capacitance of the anode foil.
[0003] There are several methods for increasing the surface of aluminum foil in the prior art. The first is to expand the surface area by corrosion, which is commonly used in mechanical, physical, chemical and electrochemical methods. The disadvantage of the above corrosion methods is that the corrosion rate is too low, and it is easily affected by various factors during the process of corrosion along the grain boundary, which makes the corrosion coefficient too high, thereby reducing the mechanical strength of the aluminum foil, and the increase in surface area is not large, so it is difficult to develop. Therefore, aluminum powder sintering technology is mostly used in the prior art, but this technology causes the oxide layer of fine pure aluminum particles to be too thick during the formation stage and the sintering stage, and too much mixed and dispersed medium leads to poor contact between pure aluminum particles, thereby generating holes in the sintered foil and causing the electric field to concentrate. Summary of the invention
[0004] In order to overcome the problem that the formation of oxide layer of powder sintered foil is difficult to control during sintering and chemical formation, and too much added material causes poor contact of pure aluminum particles, resulting in a decrease in the specific capacitance of the anode foil, the present invention provides an aluminum electrolytic capacitor sintered foil and a preparation method thereof, and the specific scheme is as follows: First, the preparation method of the aluminum electrolytic capacitor sintered foil includes the following specific preparation steps: S1, performing a deoxidation pretreatment on pure aluminum particles to obtain pure aluminum powder, and placing the pure aluminum powder in a solvent to form an aluminum powder dispersion, adding europium salt to the aluminum powder dispersion to obtain a first dispersion, and then adding a deposition agent to form a deposit on the surface of the aluminum powder; S2, filtering out the aluminum powder with sediment on the surface of the first dispersion, and re-dispersing it with a binder in a solvent to obtain a second dispersion, dispersing sodium hydride in the solvent to obtain a sodium hydride dispersion, dropping the sodium hydride dispersion into the second dispersion, mixing, and performing high-speed ball milling to form a slurry, coating the slurry on both sides of the base aluminum foil and drying to form a sintered foil precursor; S3, placing the sintered foil precursor in an oxygen-free atmosphere for multiple heat treatments to obtain an aluminum powder sintered foil; S4, performing a chemical treatment on the aluminum powder sintered foil, wherein the voltage of the chemical treatment is 220V, and then performing an oxidative heat treatment to obtain an anodized sintered foil; The europium salt is one of europium fluoride or europium chloride, and the weight ratio of the europium salt to the pure aluminum powder is 3-9:40; The deposition agent is one of ammonium hydroxide, sodium sulfide or sodium phosphate, and the molar ratio of the deposition agent to the europium salt is 1.1-2:1.
[0005] The present application adds europium salt to the dispersion of aluminum powder so that a thin layer of europium precipitate is attached to the surface of pure aluminum particles. During the subsequent sintering and chemical treatment, the europium element enters the lattice of aluminum and aluminum oxide, and strengthens the strength of the sintered foil in the form of a solid solution. In the process of forming a slurry from the second dispersion, sodium hydride is added. During the sintering process, the relevant metal oxides are reduced, the content of the single metal oxide film is reduced, and the obstacles to the subsequent generation of the composite oxide film are reduced, so that the proportion of the composite oxide film is increased. The europium element enhances its connection and growth speed during the formation of the aluminum oxide lattice, so that the porous structure of the sintered foil has sufficient connection strength and specific capacitance, and its dielectric properties are enhanced while reducing the thickness of the oxide film.
[0006] The europium salt used in the present application is europium fluoride or europium chloride. Fluoride ions have low solubility in aluminum and are relatively mild in the microenvironment, while chloride ions have low solubility in aluminum and are not as affected by nitrate ions. Accordingly, the precipitant used selects ammonium hydroxide as the main reaction reagent, in which hydroxide reacts with europium ions to generate europium hydroxide, which will generate europium oxide after subsequent heating. The reaction between ammonium hydroxide and pure aluminum needs to reach 60°C, so the temperature during the precipitation treatment will not lead to the reduction and dissolution of pure aluminum.
[0007] The present application further adds sodium hydride to the second dispersion, and then forms a slurry through high-speed ball milling, which not only breaks the sodium hydride into smaller textures, but also improves the dispersion effect, thereby facilitating the formation of a reducing atmosphere in the subsequent sintering process to reduce the single oxide film.
[0008] Preferably, the solvent in step S1 is one of N-methylpyrrolidone, dimethylformamide, dimethyl carbonate or ethylene glycol methyl ether.
[0009] Preferably, the adhesive in step S2 is one of polyvinylidene fluoride, lithium polyacrylate, polyvinyl acid, carboxymethyl cellulose or polytetrafluoroethylene, and the mass ratio of the adhesive to the aluminum powder is 1:6-10.
[0010] Preferably, the particle size of the pure aluminum particles in step S1 is 2-5 μm, and the deoxidation pretreatment includes dilute nitric acid leaching and ultrasonic cleaning.
[0011] Preferably, the concentration of the dilute nitric acid leaching is 4%-8%, and the ultrasonic frequency of the ultrasonic cleaning is 72kHz and the power is 25-30W / L.
[0012] Preferably, the weight ratio of the solvent to pure aluminum in the first dispersion is 4:2-3, and the weight ratio of the solvent to aluminum powder in the second dispersion is 5:2-3.
[0013] Preferably, in step S2, the solid-liquid ratio of sodium hydride dispersed in the solvent is 1 g:20 mL, and the weight ratio of the sodium hydride to the aluminum powder is 3-7:100.
[0014] Preferably, the multiple heat treatments include pre-sintering treatment, sintering treatment, reduction treatment and high-temperature connection treatment, wherein the pre-sintering treatment is low-temperature drying at 160°C for 6 hours, the sintering treatment is insulation at 450°C for 2 hours, the reduction treatment is reduction at 820°C for 5 minutes, and the high-temperature connection treatment is high-temperature sintering at 640°C for 4 hours.
[0015] After using sodium hydride as an additive, the present application increases the heat treatment temperature by a reduction treatment of up to 820°C for 5 minutes. This step can quickly decompose the sodium hydride to form a reducing atmosphere, and the europium element on the surface of the pure aluminum particles can initially prevent the direct melting between the pure aluminum particles, and then the connection between the pure aluminum particles is not affected after rapid cooling. In addition, due to the high melting point of europium oxide, this step accelerates the speed at which the europium element enters the aluminum oxide lattice, thereby improving the strength and generation speed of the composite oxide film.
[0016] Preferably, the voltage of the chemical formation treatment is 220V.
[0017] 10. An anodized sintered foil prepared by the method for preparing an aluminum electrolytic capacitor sintered foil according to any one of claims 1 to 9, characterized in that the thickness of the base aluminum foil in the sintered foil is 20-30 μm, and the thickness of the sintered part of the sintered foil powder is 60-80 μm.
[0018] The beneficial effects of the present invention are: 1. The present application mainly cooperates in three aspects to greatly improve the specific capacitance of aluminum electrolytic capacitors. First, europium salt is added, and then a precipitant is used to precipitate the europium salt on the surface of pure aluminum particles in the dispersion, so that a europium thin film is uniformly formed on the surface of the aluminum powder. After the film is formed, the europium element can enter the lattice of aluminum oxide in the subsequent sintering and formation steps, thereby forming a composite oxide film, so that the composite oxide film has strong corrosion resistance, increased resistance to excessive corrosion, and better specific capacitance; secondly, sodium hydride is added to the adhesive, evenly distributed between the pure aluminum particles, and the sodium hydride is retained during the removal of the adhesive in the second stage, and then decomposed after heating to 800°C. The reducing atmosphere formed can promote the thin oxide film on the surface of the aluminum powder to be reduced to pure aluminum, thereby accelerating the sintering process, promoting the improvement of the conductivity between the aluminum powders, and reducing the thickness of the oxide film. After this step, the subsequent formation will obtain a higher content of the composite oxide film, thereby achieving a better specific capacitance effect with a thinner oxide film.
[0019] 2. The purpose of the pre-sintering treatment is to dry at 160℃ at low temperature to remove the solvent, and the purpose of the medium temperature insulation at 450℃ is to remove the adhesive. Then the temperature is raised to 820℃ to reduce the sodium hydride, and finally the aluminum powder is sintered at 640℃ for 4h to form adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic diagram of a curve graph of specific capacitance of the present invention is shown.
[0021] Figure 2 The present invention is a schematic diagram of drawing a curve graph of compressive strength. DETAILED DESCRIPTION
[0022] The following will refer to the attached Figure 1 to Figure 2 The embodiments of the present invention are described in detail. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0023] The concentrations of the deposition agents used in the examples of this application are as follows: The concentration of ammonium hydroxide is 0.1 mol / L, sodium sulfide is 0.02 mol / L, sodium phosphate is 0.1 mol / L, and sodium hydroxide is 0.01 mol / L.
[0024] Preparation Example 1 Preparation of sintered foil precursor S1. Select pure aluminum particles with a particle size of 3 μm, use a dilute nitric acid solution with a concentration of 6% to acid-leach the pure aluminum particles to remove the surface oxide layer, then set the ultrasonic frequency to 72 kHz and the power to 25 W / L to perform ultrasonic cleaning on the pure aluminum particles to obtain pure aluminum powder, mix the pure aluminum powder with N-methylpyrrolidone at a weight ratio of 2.5:4 to form an aluminum powder dispersion, add europium fluoride to the aluminum powder dispersion to mix to obtain a first dispersion, the weight ratio of europium fluoride to pure aluminum powder is 6:40, and ammonium hydroxide and europium fluoride are added to ammonium hydroxide at a molar ratio of 1.5:1 to form a deposit on the surface of the aluminum powder.
[0025] S2. Filter out the aluminum powder with sediment on the surface in the first dispersion, redisperse the aluminum powder and polyvinylidene fluoride in N-methylpyrrolidone to obtain a second dispersion, the mass ratio of polyvinylidene fluoride to aluminum powder is 1:8, the weight ratio of N-methylpyrrolidone to aluminum powder is 2:1, weigh sodium hydride according to the weight ratio of sodium hydride to aluminum powder of 5:100, and then disperse the sodium hydride in a solvent at a solid-liquid ratio of 1g:20mL to obtain a sodium hydride dispersion, drop the sodium hydride dispersion into the second dispersion, mix, perform high-speed ball milling to form a slurry, apply the slurry to both sides of the base aluminum foil and dry it, the thickness of the base aluminum foil in the sintered foil is 25μm, and the thickness of the sintered part of the sintered foil powder is 70μm, to form a sintered foil precursor.
[0026] Preparation Example 2 Preparation of sintered foil precursor S1. Select pure aluminum particles with a particle size of 2 μm, use a dilute nitric acid solution with a concentration of 4% to acid-leach the pure aluminum particles to remove the surface oxide layer, then set the ultrasonic frequency to 72 kHz and the power to 28 W / L to perform ultrasonic treatment and cleaning on the pure aluminum particles to obtain pure aluminum powder, mix the pure aluminum powder with dimethylformamide in a weight ratio of 1:2 to form an aluminum powder dispersion, add europium chloride to the aluminum powder dispersion to mix to obtain a first dispersion, the weight ratio of europium chloride to pure aluminum powder is 3:40, and then add sodium sulfide in a molar ratio of 1.1:1 to form a deposit on the surface of the aluminum powder; S2. Filter out the aluminum powder with sediment on the surface in the first dispersion, and redisperse the aluminum powder and lithium polyacrylate in dimethylformamide to obtain a second dispersion, wherein the mass ratio of lithium polyacrylate to aluminum powder is 1:6, and the weight ratio of dimethylformamide to aluminum powder is 5:2. Sodium hydride is weighed according to a weight ratio of sodium hydride to aluminum powder of 3:100, and then sodium hydride is dispersed in dimethylformamide at a solid-liquid ratio of 1 g:20 mL to obtain a sodium hydride dispersion, and the sodium hydride dispersion is added dropwise to the second dispersion to mix, and high-speed ball milling is performed to form a slurry, and the slurry is coated on both sides of a base aluminum foil and dried, wherein the thickness of the base aluminum foil in the sintered foil is 20 μm, and the thickness of the sintered part of the sintered foil powder is 60 μm, to form a sintered foil precursor.
[0027] Preparation Example 3 Preparation of sintered foil precursor S1. Select pure aluminum particles with a particle size of 5 μm, use a dilute nitric acid solution with a concentration of 8% to acid-leach the pure aluminum particles to remove the surface oxide layer, then set the ultrasonic frequency to 72 kHz and the power to 30 W / L to perform ultrasonic treatment and cleaning on the pure aluminum particles to obtain pure aluminum powder, mix the pure aluminum powder with dimethyl carbonate in a weight ratio of 3:4 to form an aluminum powder dispersion, add europium fluoride to the aluminum powder dispersion to mix to obtain a first dispersion, the weight ratio of europium salt to pure aluminum powder is 9:40, and then add sodium phosphate in a molar ratio of 2:1 to form a deposit on the surface of the aluminum powder; S2. Filter out the aluminum powder with sediment on the surface in the first dispersion, and redisperse the aluminum powder and polyvinyl acid in dimethyl carbonate to obtain a second dispersion, wherein the mass ratio of polyvinyl acid to aluminum powder is 1:10, and the weight ratio of dimethyl carbonate to aluminum powder is 5:3. Sodium hydride is weighed according to a weight ratio of sodium hydride to aluminum powder of 7:100, and then sodium hydride is dispersed in a solvent at a solid-liquid ratio of 1 g:20 mL to obtain a sodium hydride dispersion, and the sodium hydride dispersion is added dropwise to the second dispersion to mix, and high-speed ball milling is performed to form a slurry, and the slurry is coated on both sides of a base aluminum foil and dried, wherein the thickness of the base aluminum foil in the sintered foil is 30 μm, and the thickness of the sintered part of the sintered foil powder is 80 μm, to form a sintered foil precursor.
[0028] Preparation Example 4 - Europium Salt Using Europium Nitrate Preparation of sintered foil precursor S1. Select pure aluminum particles with a particle size of 3 μm, use a dilute nitric acid solution with a concentration of 6% to acid-leach the pure aluminum particles to remove the surface oxide layer, then set the ultrasonic frequency to 72 kHz and the power to 25 W / L to perform ultrasonic cleaning on the pure aluminum particles to obtain pure aluminum powder, mix the pure aluminum powder with N-methylpyrrolidone at a weight ratio of 2.5:4 to form an aluminum powder dispersion, add europium nitrate to the aluminum powder dispersion to mix to obtain a first dispersion, the weight ratio of europium nitrate to pure aluminum powder is 6:40, and ammonium hydroxide and europium nitrate are added to ammonium hydroxide at a molar ratio of 1.5:1 to form a deposit on the surface of the aluminum powder.
[0029] S2. Filter out the aluminum powder with sediment on the surface in the first dispersion, redisperse the aluminum powder and polyvinylidene fluoride in N-methylpyrrolidone to obtain a second dispersion, the mass ratio of polyvinylidene fluoride to aluminum powder is 1:8, the weight ratio of N-methylpyrrolidone to aluminum powder is 2:1, weigh sodium hydride according to the weight ratio of sodium hydride to aluminum powder of 5:100, and then disperse the sodium hydride in a solvent at a solid-liquid ratio of 1g:20mL to obtain a sodium hydride dispersion, drop the sodium hydride dispersion into the second dispersion, mix, perform high-speed ball milling to form a slurry, apply the slurry to both sides of the base aluminum foil and dry it, the thickness of the base aluminum foil in the sintered foil is 25μm, and the thickness of the sintered part of the sintered foil powder is 70μm, to form a sintered foil precursor.
[0030] Preparation Example 5 - Precipitation using sodium hydroxide as the precipitant Preparation of sintered foil precursor S1. Select pure aluminum particles with a particle size of 3 μm, use a dilute nitric acid solution with a concentration of 6% to acid-leach the pure aluminum particles to remove the surface oxide layer, then set the ultrasonic frequency to 72 kHz and the power to 25 W / L to perform ultrasonic cleaning on the pure aluminum particles to obtain pure aluminum powder, mix the pure aluminum powder with N-methylpyrrolidone at a weight ratio of 2.5:4 to form an aluminum powder dispersion, add europium fluoride to the aluminum powder dispersion to mix to obtain a first dispersion, the weight ratio of europium fluoride to pure aluminum powder is 6:40, and add sodium hydroxide to ammonium hydroxide and europium fluoride at a molar ratio of 1.5:1 to form a deposit on the surface of the aluminum powder.
[0031] The remaining steps are the same as those in Preparation Example 1.
[0032] Preparation Example 6 - Instead of using europium salt, europium oxide was directly used for mixing Preparation of sintered foil precursor S1. Select pure aluminum particles with a particle size of 3 μm, use a dilute nitric acid solution with a concentration of 6% to acid-leach the pure aluminum particles to remove the surface oxide layer, then set the ultrasonic frequency to 72 kHz and the power to 25 W / L to perform ultrasonic cleaning on the pure aluminum particles to obtain pure aluminum powder, mix the pure aluminum powder with N-methylpyrrolidone at a weight ratio of 2.5:4 to form an aluminum powder dispersion, add europium oxide to the aluminum powder dispersion to mix to obtain a first dispersion, the weight ratio of europium oxide to pure aluminum powder is 5:40, and then perform ball milling dispersion to obtain homogeneous aluminum powder.
[0033] S2. Filter out the homogeneous aluminum powder in the first dispersion, and redisperse the homogeneous aluminum powder and polyvinylidene fluoride in N-methylpyrrolidone to obtain a second dispersion, wherein the mass ratio of polyvinylidene fluoride to homogeneous aluminum powder is 1:8, and the weight ratio of N-methylpyrrolidone to homogeneous aluminum powder is 2:1. Weigh sodium hydride at a weight ratio of 5:100 between sodium hydride and homogeneous aluminum powder, and then disperse sodium hydride in a solvent at a solid-liquid ratio of 1 g:20 mL to obtain a sodium hydride dispersion, dropwise add the sodium hydride dispersion into the second dispersion, mix, and perform high-speed ball milling to form a slurry, apply the slurry to both sides of the base aluminum foil and dry, wherein the thickness of the base aluminum foil in the sintered foil is 25 μm, and the thickness of the sintered part of the sintered foil powder is 70 μm, to form a sintered foil precursor.
[0034] Preparation Example 7 - No sodium hydride was added to the second dispersion Preparation of sintered foil precursor S1. Select pure aluminum particles with a particle size of 3 μm, use a dilute nitric acid solution with a concentration of 6% to acid-leach the pure aluminum particles to remove the surface oxide layer, then set the ultrasonic frequency to 72 kHz and the power to 25 W / L to perform ultrasonic cleaning on the pure aluminum particles to obtain pure aluminum powder, mix the pure aluminum powder with N-methylpyrrolidone at a weight ratio of 2.5:4 to form an aluminum powder dispersion, add europium fluoride to the aluminum powder dispersion to mix to obtain a first dispersion, the weight ratio of europium fluoride to pure aluminum powder is 6:40, and ammonium hydroxide and europium fluoride are added to ammonium hydroxide at a molar ratio of 1.5:1 to form a deposit on the surface of the aluminum powder.
[0035] S2. Filter out the aluminum powder with sediment on the surface in the first dispersion, redisperse the aluminum powder and polyvinylidene fluoride in N-methylpyrrolidone to obtain a second dispersion, wherein the mass ratio of polyvinylidene fluoride to aluminum powder is 1:8, and the weight ratio of N-methylpyrrolidone to aluminum powder is 2:1, and perform high-speed ball milling to form a slurry. Apply the slurry to both sides of the base aluminum foil and dry it. The thickness of the base aluminum foil in the sintered foil is 25 μm, and the thickness of the sintered part of the sintered foil powder is 70 μm, thereby forming a sintered foil precursor.
[0036] Example 1 Aluminum electrolytic capacitor sintered foil The sintered foil precursor in Preparation Example 1 was placed in a vacuum furnace with an oxygen-free atmosphere, first heated to 160°C and dried at low temperature for 6 hours to remove the solvent, then heated to 450°C and sintered for 2 hours to remove the binder, then quickly heated to 820°C for high-temperature treatment of sodium hydride for 5 minutes, and quickly cooled to 640°C for sintering for 4 hours to form a preliminary composite oxide film to obtain aluminum powder sintered foil.
[0037] The aluminum powder sintered foil was subjected to chemical treatment using a voltage of 220V to allow the preliminary composite oxide film to further grow, and then an oxidative heat treatment was performed at a temperature of 550°C to obtain a complete composite oxide film to form an anodized sintered foil.
[0038] Example 2 Aluminum electrolytic capacitor sintered foil The sintered foil precursor in Preparation Example 2 was placed in a vacuum furnace with an oxygen-free atmosphere, first heated to 160°C and dried at low temperature for 6 hours to remove the solvent, then heated to 450°C and sintered for 2 hours to remove the binder, then quickly heated to 820°C for high-temperature treatment of sodium hydride for 5 minutes, and quickly cooled to 640°C for sintering for 4 hours to form a preliminary composite oxide film to obtain aluminum powder sintered foil.
[0039] The aluminum powder sintered foil was subjected to chemical treatment using a voltage of 220V to allow the preliminary composite oxide film to further grow, and then an oxidative heat treatment was performed at a temperature of 550°C to obtain a complete composite oxide film to form an anodized sintered foil.
[0040] Example 3 Aluminum electrolytic capacitor sintered foil The sintered foil precursor in Preparation Example 3 was placed in a vacuum furnace with an oxygen-free atmosphere, first heated to 160°C and dried at low temperature for 6 hours to remove the solvent, then heated to 450°C and sintered for 2 hours to remove the binder, then quickly heated to 820°C for high-temperature treatment of sodium hydride for 5 minutes, and quickly cooled to 640°C for sintering for 4 hours to form a preliminary composite oxide film to obtain aluminum powder sintered foil.
[0041] The aluminum powder sintered foil was subjected to chemical treatment using a voltage of 220V to allow the preliminary composite oxide film to further grow, and then an oxidative heat treatment was performed at a temperature of 550°C to obtain a complete composite oxide film to form an anodized sintered foil.
[0042] Comparative Example 1 Aluminum electrolytic capacitor sintered foil The sintered foil precursor in Preparation Example 4 was placed in a vacuum furnace with an oxygen-free atmosphere, first heated to 160°C and dried at low temperature for 6 hours to remove the solvent, then heated to 450°C and sintered for 2 hours to remove the binder, then quickly heated to 820°C for high-temperature treatment of sodium hydride for 5 minutes, and quickly cooled to 640°C for sintering for 4 hours to form a preliminary composite oxide film to obtain aluminum powder sintered foil.
[0043] The aluminum powder sintered foil was subjected to chemical treatment using a voltage of 220V to allow the preliminary composite oxide film to further grow, and then an oxidative heat treatment was performed at a temperature of 550°C to obtain a complete composite oxide film to form an anodized sintered foil.
[0044] Comparative Example 2 Aluminum electrolytic capacitor sintered foil The sintered foil precursor in Preparation Example 5 was placed in a vacuum furnace with an oxygen-free atmosphere, first heated to 160°C and dried at low temperature for 6 hours to remove the solvent, then heated to 450°C and sintered for 2 hours to remove the binder, then quickly heated to 820°C for high-temperature treatment of sodium hydride for 5 minutes, and quickly cooled to 640°C for sintering for 4 hours to form a preliminary composite oxide film to obtain aluminum powder sintered foil.
[0045] The aluminum powder sintered foil was subjected to chemical treatment using a voltage of 220V to allow the preliminary composite oxide film to further grow, and then an oxidative heat treatment was performed at a temperature of 550°C to obtain a complete composite oxide film to form an anodized sintered foil.
[0046] Comparative Example 3 Aluminum electrolytic capacitor sintered foil The sintered foil precursor in Preparation Example 6 was placed in a vacuum furnace with an oxygen-free atmosphere, first heated to 160°C and dried at low temperature for 6 hours to remove the solvent, then heated to 450°C and sintered for 2 hours to remove the binder, then quickly heated to 820°C for high-temperature treatment of sodium hydride for 5 minutes, and quickly cooled to 640°C for sintering for 4 hours to form a preliminary composite oxide film to obtain aluminum powder sintered foil.
[0047] The aluminum powder sintered foil was subjected to chemical treatment using a voltage of 220V to allow the preliminary composite oxide film to further grow, and then an oxidative heat treatment was performed at a temperature of 550°C to obtain a complete composite oxide film to form an anodized sintered foil.
[0048] Comparative Example 4 Aluminum electrolytic capacitor sintered foil The sintered foil precursor in Preparation Example 7 was placed in a vacuum furnace with an oxygen-free atmosphere, first heated to 160°C and dried at low temperature for 6 hours to remove the solvent, then heated to 450°C and sintered for 2 hours to remove the binder, then quickly heated to 820°C for high-temperature treatment of sodium hydride for 5 minutes, and quickly cooled to 640°C for sintering for 4 hours to form a preliminary composite oxide film to obtain aluminum powder sintered foil.
[0049] The aluminum powder sintered foil was subjected to chemical treatment using a voltage of 220V to allow the preliminary composite oxide film to further grow, and then an oxidative heat treatment was performed at a temperature of 550°C to obtain a complete composite oxide film to form an anodized sintered foil.
[0050] Comparative Example 5: No heating above 820°C Aluminum electrolytic capacitor sintered foil The sintered foil precursor in Preparation Example 1 was placed in a vacuum furnace with an oxygen-free atmosphere, first heated to 160°C and dried at low temperature for 6 hours to remove the solvent, then heated to 450°C and sintered for 2 hours to remove the binder, and then heated to 640°C and sintered for 4 hours to form a preliminary composite oxide film to obtain aluminum powder sintered foil.
[0051] The aluminum powder sintered foil was subjected to chemical treatment using a voltage of 220V to allow the preliminary composite oxide film to further grow, and then an oxidative heat treatment was performed at a temperature of 550°C to obtain a complete composite oxide film to form an anodized sintered foil.
[0052] Experiments and data The anodized sintered foils prepared in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to specific capacitance test, voltage withstand test and compressive strength test, and the test methods are as follows: Specific capacitance test: Use YTV-01M anode foil TV characteristic tester for testing.
[0053] Withstand voltage test: Use a withstand voltage tester to test the anodized sintered foil and read the data.
[0054] Compressive strength test: Tested in accordance with GB / T 4740-1999 standard.
[0055] The test data is shown in Table 1 below: Table 1
[0056] Draw a curve graph for the above specific capacitance, such as Figure 1 As shown, the compressive strength is plotted as Figure 2 shown.
[0057] analyze According to the data in Table 1 of Examples 1 to 3, the anodized sintered foil prepared in the examples of the present application has a high specific capacitance, a relatively stable withstand voltage, and a high compressive strength, and will not have poor connection strength due to incomplete sintering connection.
[0058] According to the data of Comparative Example 1 in Table 1, it can be seen that the specific capacitance of Comparative Example 1 decreases significantly, the withstand voltage remains unchanged, and the compressive strength decreases to a certain extent. The europium salt used in Comparative Example 1 is nitrate, which means that nitrate has a greater impact on pure aluminum particles, and may cause more local corrosion on the surface of pure aluminum particles. After the subsequent precipitant is used, it will affect the deposition effect, thereby causing the bonding strength between the europium element and the pure aluminum surface to deteriorate.
[0059] According to the experimental data of Comparative Example 2 in Table 1, the specific capacitance of Comparative Example 2 decreases to a certain extent, and the voltage resistance and compressive strength are good. The deposition agent used in Comparative Example 2 is sodium hydroxide. It can be seen that the use of sodium hydroxide deposition agent will cause the europium to adhere loosely, but it will form a compound layer with pure aluminum, thereby having better voltage resistance.
[0060] According to the experimental data of Comparative Example 3 in Table 1, it can be seen that the specific capacitance of Comparative Example 3 decreases significantly, the withstand voltage also decreases significantly, and the compressive strength is poor. Comparative Example 3 does not use europium salt, but directly uses europium oxide, so that the pure aluminum particles and europium oxide cannot effectively form adhesion, and because the processing temperature is low and cannot exceed the melting point of aluminum, the europium element cannot enter the aluminum phase lattice, thereby failing to increase its strength and specific electrical properties.
[0061] According to the experimental data of Comparative Example 4 in Table 1, the specific capacitance of Comparative Example 4 decreases slightly, and the withstand voltage and compressive strength decrease significantly. In the preparation process of Comparative Example 4, sodium hydride is not added, so a reducing atmosphere cannot be generated in the subsequent heating process, thereby failing to reduce the thickness of the aluminum oxide layer, making it more difficult for europium to enter the crystal lattice, resulting in poor quality of the anodized sintered foil and low data.
[0062] According to the experimental data of Comparative Example 5 in Table 1, the specific capacitance and withstand voltage of Comparative Example 5 decreased slightly, and the compressive strength decreased to a large extent. Comparative Example 5 was not heated at 820 degrees Celsius, resulting in the failure of sodium hydride to decompose and the formation of a reducing atmosphere. In addition, the presence of impurities significantly reduced its compressive strength.
[0063] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. A method for preparing a sintered foil for an aluminum electrolytic capacitor, characterized in that: The method comprises the following specific preparation steps: S1, performing a deoxidation pretreatment on pure aluminum particles to obtain pure aluminum powder, and placing the pure aluminum powder in a solvent to form an aluminum powder dispersion, adding europium salt to the aluminum powder dispersion to obtain a first dispersion, and then adding a deposition agent to form a deposit on the surface of the aluminum powder; S2, filtering out the aluminum powder with sediment on the surface of the first dispersion, and re-dispersing it with a binder in a solvent to obtain a second dispersion, dispersing sodium hydride in the solvent to obtain a sodium hydride dispersion, dropping the sodium hydride dispersion into the second dispersion, mixing, and performing high-speed ball milling to form a slurry, coating the slurry on both sides of the base aluminum foil and drying to form a sintered foil precursor; S3, placing the sintered foil precursor in an oxygen-free atmosphere for multiple heat treatments to obtain an aluminum powder sintered foil; S4, performing chemical treatment on the aluminum powder sintered foil, and then performing oxidation heat treatment to obtain an anodized sintered foil; The europium salt is one of europium fluoride or europium chloride, and the weight ratio of the europium salt to the pure aluminum powder is 3-9:40; The deposition agent is one of ammonium hydroxide, sodium sulfide or sodium phosphate, and the molar ratio of the deposition agent to the europium salt is 1.1-2:
1.
2. The method for preparing a sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The solvent in step S1 is one of N-methylpyrrolidone, dimethylformamide, dimethyl carbonate or ethylene glycol methyl ether.
3. The method for preparing a sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The adhesive in step S2 is one of polyvinylidene fluoride, lithium polyacrylate, polyvinyl acid, carboxymethyl cellulose or polytetrafluoroethylene, and the mass ratio of the adhesive to the aluminum powder is 1:6-10.
4. The method for preparing a sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The particle size of the pure aluminum particles in step S1 is 2-5 μm, and the deoxidation pretreatment includes dilute nitric acid leaching and ultrasonic cleaning.
5. The method for preparing a sintered foil for an aluminum electrolytic capacitor according to claim 4, characterized in that: The concentration of the dilute nitric acid leaching is 4%-8%, and the ultrasonic frequency of the ultrasonic cleaning is 72kHz and the power is 25-30W / L.
6. The method for preparing a sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The weight ratio of the solvent to pure aluminum in the first dispersion is 4:2-3, and the weight ratio of the solvent to aluminum powder in the second dispersion is 5:2-3.
7. The method for preparing a sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: In the step S2, the solid-liquid ratio of sodium hydride dispersed in the solvent is 1 g:20 mL, and the weight ratio of the sodium hydride to the aluminum powder is 3-7:
100.
8. The method for preparing a sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The multiple heat treatments include pre-sintering treatment, sintering treatment, reduction treatment and high-temperature connection treatment, wherein the pre-sintering treatment is low-temperature drying at 160°C for 6 hours, the sintering treatment is heat preservation at 450°C for 2 hours, the reduction treatment is reduction at 820°C for 5 minutes, and the high-temperature connection treatment is high-temperature sintering at 640°C for 4 hours.
9. The method for preparing a sintered foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The voltage of the formation treatment is 220V.
10. An anodized sintered foil prepared by the method for preparing an aluminum electrolytic capacitor sintered foil according to any one of claims 1 to 9, characterized in that: The thickness of the base aluminum foil in the sintered foil is 20-30 μm, and the thickness of the powder sintering part of the sintered foil is 60-80 μm.